DRUG UTILIZATION 90% (DU90%) PROFILE OF ANTIBIOTIC FOR TREATMENT OF HOSPITALIZED PATIENTS WITH URINARY TRACT INFECTIONS AT TWO HOSPITAL IN YOGYAKARTA - Saepudin Saepudin (Universitas Islam Indonesia, 2008)
ABSTRACTUrinary tract infections (UTIs) are the most common bacterial infection and account forsignificant morbidity and health care cost. It was well accepted that data of antibiotic utilization fortreatment of infectious diseases are needed in developing antibiotic use policy. Antibiotic utilizationstudy can provide useful information for improvement of the appropriate and effective antibiotic use.This research aims to compare antibiotic utilization for treatment of hospitalized patients withurinary tract infections at two hospitals in Yogyakarta based on drug utilization 90% (DU90%)profile. Data of antibiotic prescription were obtained from patient’s medical record for patientswhich were hospitalized during 2005 at hospital A (650 beds) and B (250 beds). Quantity ofantibiotics utilization was calculated as the number of defined daily dose (DDD) per 100 bed days(BD) based on ATC/DDD system released by WHO Collaborating Centre for Drug StatisticsMethodology. The antibiotics were ranked by percentage of DDD/100BD and antibiotics thataccounted for 90% (DU90%) were determined. Total of antibiotics use for hospitalized patients withUTIs at hospital A amounts to 65.77 DDD/100 BD included 14 classes, consisted of 24 agents ofantibiotic. Total antibiotics use at hospital B amounts to 58.22 DDD/100 BD included 9 classes,consisted of 13 agents of antibiotic. Ceftriaxone was the greatest antibiotic used at both hospitals.There were 9 items of antibiotics within DU90% at hospital A and 7 item of antibiotics at hospital B.There was a difference in the utilization of antibiotics for hospitalized patients with UTIs at twohospitals in Yogyakarta based on total number of antibiotics and number of antibiotics withinDU90% segment.Keywords : Antibiotic, ATC/DDD, DU90%, Urinary Tract Infections